Metformin changes the immune microenvironment of colorectal cancer in patients with type 2 diabetes mellitus. Issue 11 (28th September 2020) - Saito, Akira; Kitayama, Joji; Horie, Hisanaga; Koinuma, Koji; Ohzawa, Hideyuki; Yamaguchi, Hironori; Kawahira, Hiroshi; Mimura, Toshiki; Lefor, Alan Kawarai; Sata, Naohiro
Abstract: Accumulating evidence suggests that metformin reduces the incidence and mortality of colorectal cancer (CRC). However, underlying mechanisms have not been fully clarified. The aim of this study was to examine the pathological characteristics of resected CRC from patients treated with metformin for type 2 diabetes mellitus (DM). In total, 267 patients with DM underwent curative colectomy for Stage I‐III CRC and 53 (19.9%) patients had been treated medically including metformin. Pathological N‐stage was significantly lower in metformin‐treated patients ( P  < .05) with prolonged disease‐free survival (DFS) ( P  < .05). Immunohistochemistry showed that the densities of CD3(+) and CD8(+) tumor‐infiltrating lymphocytes (TILs) in the invasive front area were significantly higher in 40 patients treated with metformin compared with propensity score matched cases without metformin ( P  < .05). The density of tertiary lymphoid structures (TLS) in tumor stroma was markedly increased in metformin‐treated patients ( P  < .001). In those tumors, there were more CD68(+) tumor‐associated macrophages (TAM) infiltrated ( P  < .05), while the ratio of CD163(+) M2‐phenotype was markedly reduced ( P  < .001). Stromal fibrosis tended to be suppressed by metformin intake ( P  = .051). These findings suggested that metformin drastically changes the characteristics of infiltrating immune cells in CRC and reprograms the tumor microenvironment from immunosuppressive to immunocompetent status, which may lead to suppression of microscopic tumor spread and improve the outcomes of patients with CRC and type 2 DM. Abstract : Metformin treatment is associated with fewer lymphatic metastases with prolonged disease‐free survival in patients with stage I‐III colorectal cancer and diabetes mellitus. Densities of tumor‐infiltrating CD3(+) and CD8(+) T cells and tertiary lymphoid structures are significantly increased, while the ratio of CD163(+) M2 type tumor‐associated macrophages is decreased in metformin‐treated colorectal tumor. Metformin may suppress tumor spread by changing the immunosuppressive tumor microenvironment to an immunocompetent status.